Analysis of risk factors associated with unilateral hearing loss in children who initially passed newborn hearing screening. (March 2018) - Appelbaum, Eric N.; Howell, Jessica B.; Chapman, Derek; Pandya, Arti; Dodson, Kelley M.
Abstract: Objective: To analyze 2007 Joint Committee on Infant Hearing (JCIH) risk factors in children with confirmed unilateral hearing loss (UHL) who initially passed newborn hearing screening. Methods: Retrospective record review of 16, 108 infants who passed newborn hearing screening but had one or more JCIH risk factors prompting subsequent follow-up through the universal newborn hearing screening (UNHS) program in Virginia from 2010 to 2012. The study was reviewed and qualified as exempt by the Virginia Commonwealth University Institutional Review Board (IRB) and the Virginia Department of Health. Results: Over the 2-year study period, 14896 (4.9% of total births) children passed UNHS but had the presence of one or more JCIH risk factor. Ultimately, we identified 121 babies from this group with confirmed hearing loss (0.7%), with 48 babies (0.2%) showing UHL. The most common risk factors associated with the development of confirmed UHL after passing the initial screen were neonatal indicators, craniofacial anomalies, family history, and stigmata of syndrome associated with hearing loss. Conclusion: Neonatal indicators and craniofacial anomalies were the categories most often found in children with confirmed unilateral hearing loss who initially passed their newborn hearing screen. While neonatal indicators were also the most common associated risk factor in all hearing loss, craniofacial abnormalities are relatively more common in children with UHL who initially passed newborn hearing screening. Further studies assessing the etiology underlying the hearing loss and risk factor associations are warranted.